Phα1β interaction with the Kv11.1 potassium channel in HEK293 cells transfected with the human ERG channel - João B. Calixto; Adara Aurea dos Santos; Juliano Ferreira; Alessandra Hubner Souza; Célio José de Castro Junior; Marcus Vinicius Gomez (Journal of Venomous Animals and Toxins including Tropical Diseases)
Abstract Background: This study examines the impact of Phα1β, a spider peptide derived from the venom of Phoneutria nigriventer, on the Kv11.1 potassium channel in HEK293 cells transfected with the human ERG potassium channel. Phα1β inhibits high-voltage calcium channels and acts as an antagonist of the TRPA1 receptor, both of which play crucial roles in pain transduction pathways. Over the past 15 years, our research has demonstrated the potential of Phα1β, in both its native and recombinant forms, as a promising analgesic drug through preclinical tests conducted on rodent pain models. Regulatory agencies require the evaluation of new drugs on human ERG channels. Methods: To assess hERG potassium channel inhibition, we utilized the FLIPR® Potassium Assay, a commercially available kit. The assay involved testing the effects of Phα1β alongside the well-established hERG potassium channel blocker dofetilide, which served as a positive control. The viability of HEK-293 cells was assessed using the colorimetric MTT reduction test (3-(4, dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide), whereby viable cells reduce the MTT salt, forming a formazan complex within their mitochondria, as previously described. Results: Phα1β was tested at concentrations of 56, 225, 450, and 900 pMol, resulting in a discreet inhibition of hERG potassium channel activity at higher concentrations, approximately 13.47%, with an IC50 value exceeding 900 pMol. Dofetilide, administered at concentrations ranging from 0.0001 to 10 µM, displayed a concentration-dependent inhibition of the hERG potassium channel, with a mean IC50 value of 0.1642 µM (0.1189-0.2282 µM). To evaluate cytotoxicity, HEK293-hERG cells were exposed to Phα1β concentrations of 56/900 pMol for 24 hours, resulting in no significant alteration in cell viability. Conclusion: Our findings indicate that even at high concentrations, Phα1β does not impede the functionality of the hERG potassium channel nor affect cell viability.